Accuracy of frozen-section combined with imprint and fine needle aspiration biopsy in thyroid nodules (Faculty of Medicine Universitas Indonesia, 2007)
Thyroid malignancy can be found on 5% of thyroid nodules. In order to better managed of thyroid nodules, skills to differentiate benign from malignant cases were needed. Fine needle aspiration biopsy (FNAB) was done preoperatively while frozen section (FS) and imprint cytology (IC) should be done intra-operatively. The objective of this research paper is to evaluate the diagnostic accuracy of FNAB versus frozen section combined with imprint cytology (FS+IC) in thyroid nodules at the Anatomic-Pathology Department FMUI-CM Hospital, Jakarta. This diagnostic test, used data from clinico-pathological records in Anatomic Pathology Department, Faculty of Medicine University of Indonesia / Dr.Cipto Mangunkusumo General Hospital, Jakarta, Indonesia during 1999-2003. Specimens with complete data of FNAB results, data of FS and slides of IC. All formalin fixed`specimens were reevaluated and used as the golden standard. Sensitivity, spesificity and accuracy of FS+IC were higher than FNAB (86.8% vs 73.7% ; 99.0% vs 83.9% ; 94.8% vs 80.5% respectively). If the results of FNAB were concordant with the result of FS+IC, the combined examination yields accuracy of 95.1%. The evaluation of frozen section combined with imprint cytology is very useful, because this examination significantly showed high accuracy in diagnosing thyroid malignancy. (Med J Indones 2007; 16:89-93)Keywords: thyroid nodules, FNAB, frozen section, imprint cytology, accuracy